Odpowiedź :
Odpowiedź:
zad 1
1)
3x(2x - 4) - 4x(x² + 2x - 3) = 6x² - 12x - 4x³ - 8x² + 12x = - 4x³ - 2x²
2)
(3x - 1)² - (3x - 1)(1 + 3x) = 9x² - 6x + 1 - (3x - 1)(3x + 1) =
= 9x² - 6x + 1 - (9x² - 1) = 9x² - 6x + 1 - 9x² + 1 = - 6x + 2
zad 2
1)
(5x + 1)(2 - x) + x(5x - 2) ≥ x
10x + 2 - 5x² - x + 5x² - 2x ≥ x
7x + 2 ≥ x
7x - x ≥ - 2
6x ≥ - 2
x ≥ - 2/6
x ≥ - 1/3
x ∈ < - 1/3 , + ∞ )
przedział liczbowy rozwiązania
↓-----------------------------------------------------------------------→
---------------------------⊕-------0--------------------------1-------------------------------→ x
(- 1/3)
Podaną nierówność spełniają wszystkie liczby naturalne , czyli :
0 , 1 , 2 , 3 ......................
2)
IxI < 5
x < 5 ∧ x > - 5
x ∈ ( - 5 , 5 )
przedział liczbowy rozwiązania
↓--------------------------------------------------------------------↓
----------------O-----------------------------0 ------1 --------------------------- O-------------→
(- 5) 5
zad 3
1)
6/(3 - √2) = 6(3 + √2)/[(3 - √2)(3 + √2) = 6(3 + √2)/(9 - 2) = 6(3 + √2)/7
2)
√2/(2 + √2) = 2(2 - √2)/[(2 + √2)(2 - √2)] = 2(2 - √2)/(4 - 2) =
= 2(2 - √2)/2 = 2 - √2